Plant Terpenes on Treating Cardiovascular and Metabolic Disease: A Review - Oliveira, Janaína R.; Ribeiro, Guilherme H. M.; Rezende, Luiz Fernando; Fraga-Silva, Rodrigo Araújo (Protein and Peptide Letters, 2021)
The use of medicinal plants as a therapy alternative is old as human existence itself. Nowadays, the search for effective molecules for chronic diseases treatments has increased. The cardiometabolic disorders still the main cause of death worldwide and plants may offer potential pharmacological innovative approaches to treat and prevent diseases. In the range of plant molecules are inserted the terpenes, which constituent essential elements with several pharmacological characteristics and applications, including cardiovascular and metabolic properties. Thus, the aim of the present review is to update the terpenes use on chronic disorders such as obesity, diabetes, hypertension and vascular conditions. The review includes a brief terpenes description based on the scientific literature in addition to data collected from secondary sources such as books and conference proceedings. We concluded that terpenes could act as adjuvant or main alternative treatment (when started earlier) to improve cardiometabolic diseases, contributing to reduce side effects of conventional drugs, in addition to preserving ethnopharmacological knowledge.
Keywords: terpenes